Public Perception of COVID-19 Vaccination in Italy: The Role of Trust and Experts’ Communication - Bucchi, Massimiano; Fattorini, Eliana; Saracino, Barbara (International Journal of Public Health, 2022)
Objectives: Vaccination campaigns against COVID-19 throughout the world are not only a major organisational challenge, but also a communication and social challenge. Recent data from several countries show that a relevant proportion of citizens either do not plan to be vaccinated against COVID-19 or would rather postpone their vaccination. We argue that such attitudes are not the result of generalised scepticism about vaccination, nor of generalised distrust in science. Methods: We analysed data from three survey waves on attitudes to vaccination against COVID-19 conducted in Italy in October 2020, January 2021, and May 2021 in the context of the Science in Society Monitor. Results: Positive evaluations of experts’ communication and trust in their contribution – as well as in that of health institutions, local authorities, and healthcare workers – play a key role in understanding the willingness to be vaccinated. Conclusion: Relevant implications can be drawn in terms of communication efforts and institutional strategies that are essential to build effective and inclusive vaccination campaigns.